Value creation in emerging technologies in E-Business for each stakeholder - William, Haslam (2010)
In today’s increasingly competitive global environment, producers must look for ever more innovative ways to capture market share and create differentiated offerings. On this basis, this research aims to look in depth at a number of emerging technologies and the value they create for their stakeholders. Borrowing heavily from a number of different concepts, this dissertation develops an analytical framework which is used to review four technologies: